Catalyst, preparation method thereof and preparation method of 2, 5-furandicarboxylic acid
By using the catalyst composed of single atoms composed of nickel hydroxide carriers and anchored in its lattice, the problem of difficulty preparation of 2,5-beanic acid under the existing technologies is difficult to efficiently prepare under the existing technologies, and the high stability of catalysts is achieved. Sexual and efficient catalysis reduces production costs.
Patent Information
- Application Number
- CN202411304888.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The prior art is difficult to efficiently prepare 2,5-furandicarboxylic acid under mild catalytic conditions, and the stability of nickel-based catalysts is poor, which limits the widespread application of electrocatalytic 5-hydroxymethylfurfural oxidation technology.
A catalyst composed of a nickel hydroxide carrier and a ruthenium single atom anchored in the nickel hydroxide carrier crystal lattice is used. It is combined with the nickel hydroxide carrier through Ru-O coordination bonds to improve the stability and catalytic activity of the catalyst.
The 2,5-beanic acid is efficient under mild conditions. After 20 electrolytic cycles, the catalyst still maintains good stability and high catalytic activity, which significantly reduces production costs.
Smart Images

Figure HDA0005049531040000011 
Figure HDA0005049531040000012 
Figure HDA0005049531040000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, in particular to a catalyst and a preparation method thereof and a preparation method of 2,5-furandicarboxylic acid. Background Art
[0002] With the rapid consumption of fossil resources and increasingly serious environmental problems, the development and utilization of new renewable resources has become an urgent need for social development. As a sustainable renewable carbon source in nature, biomass resources have the advantages of green production and environmental friendliness, and are considered to be a potential substitute for traditional fossil energy. Compared with direct use as fuel, converting biomass into high-value-added products or intermediates for the synthesis of fine chemicals is an effective way to maximize the use of renewable energy.
[0003] As an important biomass-based platform derivative, 5-hydroxymethylfurfural (HMF) can generate a variety of high-value-added chemicals through different catalytic conversion pathways, which are widely used in fine chemicals, fuels, food additives, medicines and other fields. In particular, 2,5-furandicarboxylic acid (FDCA) prepared by 5-hydroxymethylfurfural selective oxidation (HMFOR) can be used to replace petroleum-derived terephthalic acid as a sustainable and degradable monomer raw material for the production of bio-based polyesters, thereby promoting the establishment of a circular plastic economy. However, the thermal catalytic oxidation of 5-hydroxymethylfurfural usually requires high temperature and high pressure reaction conditions, so it is impossible to efficiently prepare 2,5-furandicarboxylic acid under mild catalytic conditions.
[0004] The electrocatalytic 5-hydroxymethylfurfural oxidation technology driven by clean electric energy can be carried out at room temperature and pressure. It can achieve efficient conversion of biomass under mild conditions and is a potential technology for achieving efficient preparation of 2,5-furandicarboxylic acid under mild conditions. The electrocatalytic 5-hydroxymethylfurfural oxidation technology requires a large number of catalyst types. In recent years, nickel-based catalysts have been proven to be efficient catalysts for the electro-oxidation of 5-hydroxymethylfurfural, which has attracted widespread attention from researchers. However, the stability of nickel-based catalysts has not been significantly improved. Currently, a large number of catalysts reported can only be recycled 5 to 10 times. The poor stability limits the widespread application of the electrocatalytic 5-hydroxymethylfurfural oxidation technology for the efficient preparation of 2,5-furandicarboxylic acid.
[0005] Therefore, research and development of a new catalyst with both high efficiency and good stability is of great significance for the electrocatalytic preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a catalyst and a preparation method thereof and a preparation method of 2,5-furandicarboxylic acid. The catalyst has excellent stability and high catalytic activity, and has high selectivity for 2,5-furandicarboxylic acid in the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural.
[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a catalyst, which is composed of a nickel hydroxide carrier and a single ruthenium atom anchored in the nickel hydroxide carrier crystal lattice;
[0009] The nickel hydroxide carrier is a layered nanosheet;
[0010] The catalyst contains Ru-O coordination bonds.
[0011] In the catalyst of the present invention, the ruthenium single atom is anchored on the nickel hydroxide carrier in a monodisperse state, and the ruthenium single atom is combined with the nickel hydroxide carrier through a Ru-O coordination bond, so that the ruthenium single atom has excellent atomic utilization.
[0012] The invention improves the electronic structure of the nickel hydroxide carrier by introducing a single ruthenium atom, so that the catalyst has excellent stability and high catalytic activity and catalytic efficiency.
[0013] Since the strong interaction between the ruthenium single atom and the nickel hydroxide carrier promotes the transfer of electrons from nickel to the ruthenium single atom, the valence state of the Ni species in the catalyst of the present invention is higher.
[0014] Preferably, the average size of the catalyst is 30-40 nm.
[0015] Preferably, the loading amount of ruthenium single atoms in the catalyst is 2wt%-4wt%.
[0016] The present invention also provides a method for preparing the above catalyst, comprising the following steps:
[0017] A nickel source, a ruthenium source, water and a sodium hydroxide aqueous solution are slowly added to a mixed solution of sodium nitrate and formamide, the pH is controlled to be 9-11, and the catalyst is obtained through heating and coprecipitation.
[0018] The above preparation method adopts a specific addition order in order to better control the monodisperse state of the active ingredient ruthenium atoms in the catalyst, and to make the overall nano size of the catalyst smaller. It is combined with the carrier nickel hydroxide through the Ru-O coordination bond, so that the stability of the catalyst is better and the catalytic activity and catalytic efficiency are good.
[0019] In the preparation method of the present invention, the content of the ruthenium source should not be too high, as too high a content will affect the stability and catalytic activity of the catalyst.
[0020] Preferably, in the present invention, the molar ratio of nickel element to ruthenium element in the nickel source and ruthenium source is (30-50):1; more preferably (35-45):1; further preferably 39:1.
[0021] Preferably, the heating temperature is 78°C-82°C; more preferably 80°C;
[0022] Preferably, the heating rate is 5-10°C / min; more preferably 5-8°C / min.
[0023] The slow addition in the above preparation method can be carried out by dropwise addition or other technical means well known to those skilled in the art.
[0024] Preferably, in the present invention, when the nickel source and the ruthenium source are added to the mixed solution of sodium nitrate and formamide, the addition rate of the nickel source and the ruthenium source is 2-8 mL / min; more preferably 4-6 mL / min; further preferably 5 mL / min.
[0025] Preferably, the nickel source is selected from nickel nitrate hexahydrate or nickel chloride hexahydrate;
[0026] The ruthenium source is selected from ruthenium trichloride hydrate or potassium chlororuthenate (III) pentahydrate.
[0027] In the above preparation method, the formamide is used as an intercalation agent, and sodium nitrate plays a role in neutralizing the charge in the intercalation. The combination of the two makes the catalyst have thinner nanosheets. The thinner the catalyst nanosheets are, the more catalytic sites are exposed, and the better the catalytic activity and catalytic efficiency are.
[0028] Preferably, the volume fraction of formamide in the mixed solution of sodium nitrate and formamide is 20-25%; more preferably 23%;
[0029] Preferably, the concentration of the sodium nitrate aqueous solution is 9-12 mmol / L; more preferably 10 mmol / L;
[0030] Preferably, the concentration of the sodium hydroxide aqueous solution is 0.3-0.6 mol / L; more preferably 0.5 mol / L.
[0031] The present invention also provides a method for preparing 2,5-furandicarboxylic acid, wherein 2,5-furandicarboxylic acid is prepared by electrocatalytic oxidation of 5-hydroxymethylfurfural;
[0032] Preferably, the catalyst for the electrocatalytic oxidation reaction is the above-mentioned catalyst or a catalyst prepared by the above-mentioned preparation method.
[0033] The catalyst is used for the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid. The reaction rate of the electrocatalytic oxidation reaction is higher, indicating that the catalyst of the present invention has higher catalytic activity.
[0034] The catalyst described in the present invention has better stability. Through the cycle test experiment, it still has good stability after 20 consecutive electrolysis cycles, the conversion rate of the reactant 5-hydroxymethylfurfural is 99.3%, the selectivity of 2,5-furandicarboxylic acid is 98.2%, and the Faraday efficiency of the reaction is 97.4%. Compared with the prior art, the catalyst provided by the present invention is composed of a nickel hydroxide carrier and a ruthenium single atom anchored in the nickel hydroxide carrier lattice; the nickel hydroxide carrier is a layered nanosheet; and the catalyst contains Ru-O coordination bonds. The catalyst has excellent stability and high catalytic activity and catalytic efficiency. It can be applied to the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural to obtain a high selectivity for 2,5-furandicarboxylic acid, and the catalyst of the reaction can be used repeatedly. After 20 consecutive electrolysis cycles, it still has good stability, significantly reducing the cost of efficient production of 2,5-furandicarboxylic acid, and is more conducive to environmental protection and maximization of atomic utilization, and has potential application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A transmission electron micrograph of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1;
[0036] Figure 2 A high-resolution transmission electron micrograph corrected for spherical aberration of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1;
[0037] Figure 3 X-ray diffraction patterns of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 and the pure nickel hydroxide catalyst;
[0038] Figure 4 X-ray photoelectron spectra of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 and the pure nickel hydroxide catalyst;
[0039] Figure 5 The X-ray absorption fine structure spectrum expansion edge of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 and the reference sample ruthenium foil and ruthenium dioxide (RuO2);
[0040] Figure 6 The current density curves of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 and pure nickel hydroxide loaded on nickel foam at different potentials;
[0041] Figure 7 The concentration variation diagram of the reactants, products and intermediate products obtained under different transfer charge amounts of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1;
[0042] Figure 8 The graph shows the change in conversion rate of 5-hydroxymethylfurfural, selectivity of 2,5-furandicarboxylic acid and Faraday efficiency of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 during 20 consecutive electrolysis cycles. DETAILED DESCRIPTION
[0043] In order to further illustrate the present invention, the ruthenium single atom / nickel hydroxide catalyst provided by the present invention and its preparation method and application are described in detail below in conjunction with examples.
[0044] 1. Preparation of Ruthenium Single Atom / Nickel Hydroxide Catalyst
[0045] Example 1
[0046] The present invention provides a ruthenium single atom / nickel hydroxide catalyst with an average size of 30-40 nanometers. The synthesis method thereof is as follows:
[0047] 123.6 mL of 10 mmol / L sodium nitrate aqueous solution and 36.8 mL of formamide solution were mixed and heated in a water bath and heated to 80° C. with magnetic stirring at a heating rate of 5° C. / min and a magnetic stirring speed of 300 rpm / min. The volume fraction of the formamide solution in the mixed solution was 23%.
[0048] 1.83mmol of nickel nitrate hexahydrate and 0.094mmol of ruthenium trichloride hydrate were mixed and dissolved in 100mL of deionized water to obtain 100mL of a mixed solution. 2g of sodium hydroxide solid was dissolved in 100mL of deionized water to obtain a 0.5mol / L sodium hydroxide aqueous solution. 80mL of the mixed solution of nickel nitrate hexahydrate and ruthenium trichloride hydrate was divided into two 40mL solutions and injected into the mixed solution of the above sodium nitrate aqueous solution and formamide solution at a rate of 5mL / min. During the injection process, sodium hydroxide aqueous solution was added dropwise to adjust the pH to 9-11. After 8min, the injection was completed, and sodium hydroxide aqueous solution was added dropwise at a uniform speed for 2min (the purpose of adding sodium hydroxide aqueous solution again was to make the coprecipitation reaction of sodium hydroxide with nickel ions and ruthenium ions more complete). The reaction was completed, and nitrogen was passed into the obtained mixed solution, and magnetic stirring was performed for about 3 hours until the solution temperature reached room temperature.
[0049] The obtained sample was separated by suction filtration and washed three times with deionized water. The final product was evenly dispersed with a small amount of deionized water and freeze-dried at -45°C overnight to finally obtain a ruthenium single atom / nickel hydroxide catalyst, in which the loading amount of ruthenium single atoms in the catalyst was 2.68wt%.
[0050] The transmission electron microscope image of the ruthenium single atom / nickel hydroxide catalyst prepared in this example is as follows: Figure 1 As shown, the spherical aberration corrected high-resolution transmission electron microscopy image is as follows Figure 2 As shown, Figure 1 The ultra-thin nanosheets are single-atom ruthenium / nickel hydroxide catalysts. Figure 2 The ruthenium atoms are monodispersed and anchored on the nickel hydroxide substrate.
[0051] The X-ray diffraction patterns of the ruthenium single atom / nickel hydroxide catalyst and the pure nickel hydroxide catalyst are as follows: Figure 3 As shown in Figure 2, the X-ray diffraction patterns of the two catalysts are basically the same, indicating that the introduction of ruthenium atoms has no effect on the substrate. Figure 4 As shown in Figure 1, the Ni 2p peak indicates that the Ni species in the sample is indeed nickel hydroxide, and the Ni 2p peak binding energy of the Ru single atom / nickel hydroxide catalyst is higher than that of pure nickel hydroxide, indicating that the valence state of the Ni species in the Ru single atom / nickel hydroxide catalyst is higher, which is attributed to the strong interaction between the Ru single atom and the nickel hydroxide support, which promotes the transfer of electrons from nickel to ruthenium. Figure 5 As shown, it is shown that both the ruthenium single atom / nickel hydroxide catalyst and pure RuO2 are Ru-O coordinated, which is obviously different from the Ru-Ru coordination existing in pure ruthenium foil.
[0052] 2. Performance test experiment of ruthenium single atom / nickel hydroxide catalyst
[0053] Performance test experiment 1
[0054] Using ruthenium single atom / nickel hydroxide catalyst as the active ingredient of the electrocatalyst and the test conditions for electrochemical oxidation of 5-hydroxymethylfurfural.
[0055] 2.5 mg of ruthenium single atom / nickel hydroxide catalyst is dispersed in a mixed solution of 400 μl of ethanol and 800 μl of deionized water and ultrasonically uniformly, then 5 mg of carbon powder is added and ultrasonically uniformly for 1 hour to obtain a solution with a very small carbon powder particle diameter, and then 100 μl of 5% mass fraction Nafion solution is added and ultrasonically uniformly for 1 hour to obtain a uniform mixed solution; 60 μl of the above solution is uniformly dripped onto a 0.5×0.5 square centimeter nickel foam as a working electrode, a silver / silver chloride electrode is used as a reference electrode, and a platinum wire electrode is used as a counter electrode; the electrochemical oxidation reaction of 5-hydroxymethylfurfural to synthesize 2,5-furandicarboxylic acid is carried out in an H-type electrolytic cell, the electrolytic cell is separated from the cathode by a Nafion 115 proton exchange membrane, wherein the anode chamber is filled with 30 ml of 1 mol / L potassium hydroxide and 100 mmol / L 5-hydroxymethylfurfural electrolyte, and the cathode chamber is filled with 30 ml of 1 mol / L potassium hydroxide solution as an electrolyte.
[0056] Performance test experiment 2
[0057] Current density and product selectivity test conditions of ruthenium single atom / nickel hydroxide catalyst in the electrochemical oxidation of 5-hydroxymethylfurfural.
[0058] Under the reaction conditions of performance test experiment 1, nickel foam was used as the working electrode, and the linear sweep voltammetry method was used to test the current density of the reaction; the potential relative to the reversible hydrogen electrode was set to 1.0-1.8V, the sweep rate was 5 mV / s, and the hydrogen generated at the cathode during the reaction was discharged into the air; when the nickel foam electrode was used for testing, the effective current density generated by the reaction of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 of the present invention and the pure nickel hydroxide in the above relative reversible hydrogen electrode through the electrocatalytic oxidation of 5-hydroxymethylfurfural to generate 2,5-furandicarboxylic acid was as follows Figure 6 As shown, to achieve a current density of 100 mA / cm2, nickel hydroxide needs to reach a potential of 1.54 V relative to the reversible hydrogen electrode, while the ruthenium single atom / nickel hydroxide catalyst only needs a potential of 1.44 V relative to the reversible hydrogen electrode. The current density in the electrochemical reaction can be used to describe the electrochemical reaction rate on the electrode surface, thus proving that the ruthenium single atom / nickel hydroxide catalyst of the present invention has a better catalytic efficiency.
[0059] Under the reaction conditions of performance test experiment 1, nickel foam was used as the working electrode and constant potential test was adopted; an H-type electrolytic cell with anode and cathode separated by Nafion 115 proton exchange membrane was used for the reaction, wherein the anode chamber was filled with 20 ml of 1 mol / L potassium hydroxide and 10 mmol / L 5-hydroxymethylfurfural electrolyte, and the cathode chamber was filled with 20 ml of 1 mol / L potassium hydroxide solution as electrolyte. The relative reversible hydrogen electrode potential was set to 1.45V, and constant potential electrolysis was performed for one cycle until the charge transfer reached 120 coulombs. During the electrolysis process, 50 microliters of solution were taken out from the anode chamber for every 20 coulombs of charge transferred and diluted to 2 ml with deionized water for subsequent product selectivity analysis.
[0060] Performance test experiment 3
[0061] The selectivity test of the product of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 in the electrochemical oxidation reaction of 5-hydroxymethylfurfural was analyzed by high performance liquid chromatography; the equipment was equipped with a UV-visible detector and a 4.6 mm × 250 mm Agilent 5HC-C18 chromatographic column, the wavelength of the UV detector was set to 265 nanometers, the mobile phase was methanol and 5 mmol / L ammonium formate aqueous solution, the volume ratio of the two was 3:7, and the flow rate was 0.6 ml / min. Take 10 microliters of the above solution taken out from the anode chamber and diluted and inject it into the chromatograph and separate for 10 minutes. In one electrolysis cycle (constant potential electrolysis until the charge transfer amount reaches 120 coulombs), the concentration changes of reactants, products and intermediates are as follows Figure 7 As shown, in this cycle, the concentration of the reactant 5-hydroxymethylfurfural gradually decreases with the increase of the charge amount. At 100 coulombs, the concentration of the raw material 5-hydroxymethylfurfural is about 1 mmol / L. When the charge transfer of constant potential electrolysis reaches 120 coulombs, the reactant is basically completely converted into the product 2,5-furandicarboxylic acid. The concentration of the target product 2,5-furandicarboxylic acid gradually increases with the increase of the charge amount. At the end of electrolysis, the concentrations of the reactant 5-hydroxymethylfurfural and other intermediates are extremely low. In one electrolysis cycle, the conversion rate of the reactant 5-hydroxymethylfurfural reaches 99.7%, the selectivity of 2,5-furandicarboxylic acid is 99.0%, and the Faraday efficiency of the reaction is 98.6%.
[0062] Performance test experiment 4
[0063] The stability of ruthenium single atom / nickel hydroxide catalyst for electrochemical oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid was tested under a relative reversible hydrogen electrode potential of 1.45 V.
[0064] Under the reaction conditions of performance test experiment 1, carbon paper was used as the working electrode for constant potential test, and an H-type electrolytic cell with anode and cathode separated by Nafion 115 proton exchange membrane was used for reaction, wherein the anode chamber was filled with 20 ml of 1 mol / L potassium hydroxide and 10 mmol / L 5-hydroxymethylfurfural electrolyte, and the cathode chamber was filled with 20 ml of 1 mol / L potassium hydroxide solution as electrolyte. The potential of the relative reversible hydrogen electrode was set to 1.45V, and constant potential electrolysis was performed until the charge transfer reached 120 coulombs. The hydrogen generated at the cathode during the reaction was discharged into the air. After each electrolysis cycle, 50 microliters of solution in the anode chamber after the electrolysis was completed was taken and diluted to 2 ml, and the electrolyte in the anode chamber was quickly replaced for the next cycle of electrolysis test. After that, the solution taken out of the anode chamber after multiple electrolysis cycles was analyzed by liquid chromatography. Figure 8The present invention is a graph showing the conversion rate of 5-hydroxymethylfurfural, the selectivity of 2,5-furandicarboxylic acid and the Faraday efficiency of the reaction of the ruthenium single atom / nickel hydroxide catalyst prepared in Example 1 within 20 electrolysis cycles. The results show that the catalyst of the present invention has excellent stability. After 5 electrolysis cycles, the conversion rate of 5-hydroxymethylfurfural is 99.2%, the selectivity of 2,5-furandicarboxylic acid is 99%, and the Faraday efficiency of the reaction is 98.4%. The ruthenium single atom / nickel hydroxide catalyst exhibits good stability.
[0065] After 20 electrolysis cycles, the conversion rate of 5-hydroxymethylfurfural was 99.3%, the selectivity of 2,5-furandicarboxylic acid was 98.2%, the Faradaic efficiency of the reaction was 97.4%, and the ruthenium single atom / nickel hydroxide catalyst showed good stability.
[0066] In summary, the ruthenium single atom / nickel hydroxide catalyst of the present invention has excellent stability, still maintains good stability and high catalytic activity and catalytic efficiency after 20 electrolysis cycles, and has high 2,5-furandicarboxylic acid selectivity and Faraday efficiency in the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural, which provides new ideas for the low-cost and high-efficiency production of 2,5-furandicarboxylic acid and the wide application of 2,5-furandicarboxylic acid. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for those of ordinary skill in the art, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A catalyst, characterized in that It is composed of a nickel hydroxide support and single ruthenium atoms anchored in the nickel hydroxide support lattice; The nickel hydroxide carrier is a layered nanosheet; The catalyst contains Ru-O coordination bonds.
2. The catalyst according to claim 1, characterized in that The average size of the catalyst is 30-40 nm.
3. The catalyst according to claim 1, characterized in that The loading amount of ruthenium single atoms in the catalyst is 2 wt%-4 wt%.
4. The method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: A nickel source, a ruthenium source, water and a sodium hydroxide aqueous solution are slowly added to a mixed solution of sodium nitrate and formamide, the pH value is controlled to be 9-11, and the catalyst is obtained through heating and coprecipitation.
5. The preparation method according to claim 4, characterized in that: The molar ratio of nickel element to ruthenium element in the nickel source and ruthenium source is (30-50):
1.
6. The preparation method according to claim 4, characterized in that: The heating temperature is 78°C-82°C; The heating rate is 5-10°C / min.
7. The preparation method according to claim 4, characterized in that: When the nickel source and the ruthenium source are added to the mixed solution of sodium nitrate and formamide, the adding rate of the nickel source and the ruthenium source is 2-8 mL / min.
8. The preparation method according to claim 4, characterized in that: The nickel source is selected from nickel nitrate hexahydrate or nickel chloride hexahydrate; The ruthenium source is selected from ruthenium trichloride hydrate or potassium chlororuthenate (III) pentahydrate.
9. The preparation method according to claim 4, characterized in that: The volume fraction of formamide in the mixed solution of sodium nitrate and formamide is 20-25%, and the concentration of the sodium nitrate aqueous solution is 9-12 mmol / L; The concentration of the sodium hydroxide aqueous solution is 0.3-0.6 mol / L.
10. A method for preparing 2,5-furandicarboxylic acid, characterized in that: Preparation of 2,5-furandicarboxylic acid by electrocatalytic oxidation of 5-hydroxymethylfurfural; The catalyst for the electrocatalytic oxidation reaction is the catalyst described in any one of claims 1 to 3 or the catalyst prepared by the preparation method described in any one of claims 4 to 9.
Citation Information
Patent Citations
Hydrogen evolution catalyst with nickel hydroxide layer coated elemental ruthenium structure and preparation method thereof
CN112354544A
Preparation method of monatomic catalyst
CN114045501A
Preparation method and application of nickel hydroxide supported palladium monatomic catalyst
CN115555031A
Nickel nitride loaded Ru atomic catalyst, preparation method thereof and application of nickel nitride loaded Ru atomic catalyst as electrochemical hydrogen evolution reaction catalyst
CN115896860A
Method for synthesizing nickel-based electro-oxidation 5-hydroxymethylfurfural catalyst at room temperature with low energy consumption and application of nickel-based electro-oxidation 5-hydroxymethylfurfural catalyst
CN117107275A